Analysis of the Freestyle Swimming Skill Level of Athletes at the Lembah Lubuk Manik Swimming Club Padangsidimpuan - febby syafita putri; Wilda Agustina; Haris Fadilla Siregar; Hendro Septiadi Sihombing (Athena: Physical Education and Sports Journal, 2026)
This research seeks to evaluate the freestyle swimming proficiency of athletes from the Lembah Lubuk Manik Swimming. A total sampling method was employed, including 10 participants who were between 10-15 years old. The assessment tools utilized consisted of tests for sit up, pull up, sit and reach flexibility, kickboard usage, and freestyle swimming performance. The information obtained was processed through descriptive statistics. Findings indicated that 10% of the athletes fell into the very good category, 60% were classified as good, and 30% were considered sufficient. Overall, the athletes freestyle swimming capability was rated as good. Therefore, it can be inferred that the majority of the athletes possess proficient freestyle swimming skill, although enchancements in movement coordination, breathing strategies and physical stamina are still necessary.